DIALOGUE AND ETHICS: Can the Study of Dialogue Teach Us Something about Ethics? - Kesselring, Thomas (Journal of Dharma, 2017)
Habermas and Apel tried to give Ethics a philosophical justification by analyzing the way we realize discourses. A discourse is a special kind of a dialogue or, more generally, communication. Habermas’ and Apel’s contributions profoundly influenced German philosophy and jurisprudence. Yet, Ernst Tugendhat, a friend of Habermas, very soon pronounced the objection, that the procedure of Habermas and Apel was circular: Their definition and description of "discourse" relied implicitly to the main ethical rules, and therefore these rules can easily be recognized by analyzing the settings (or structure) of a discourse. In the following text I’ll try to show that Tugendhat’s objection is valid, but nevertheless Habermas’ and Apel’s discourse philosophies remain inspiring for everyone interested in giving Ethics a solid foundation. I will argue, however, that the central pillar of this foundation is not discourse itself, but a particular kind of co-operation ("qualified cooperation"), of which discourse is an example. The main step in my argumentation consists in showing that different kinds of communication - discourse, negotiation, debate - correspond closely to different kinds of human interaction, of which "qualified co-operation" is the basic one.